Double-alkali-activated fly ash roadbed cementing material and preparation method thereof

By using dual-alkali excitation technology of red mud, fly ash and carbide slag, the problem of high preparation cost of existing roadbed materials and insufficient solid waste recycling has been solved, and efficient solid waste recycling and excellent roadbase glue have been achieved. Condensation material properties.

CN119330620APending Publication Date: 2025-01-21TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411445178.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the preparation process of existing roadbed materials, raw materials such as excitants, reinforcers or cement lime are added, resulting in high preparation costs and inability to make full use of industrial solid waste.

Method used

Using red mud, fly ash and carbide slag as raw materials, through the double alkali compound of the alkali metal Na2O in the red mud and the alkaline earth metal CaO in the carbide slag, an alkali excitation reaction occurs with the fly ash to generate hydrated calcium aluminosilicate (C-A-S-H) With hydrated sodium aluminosilicate (N-A-S-H) gel material, it achieves synergistic gelling effect.

Benefits of technology

Significantly improve the degree of fly ash alkali stimulation reaction, improve the mechanical properties and durability of roadbed cementitious materials, reduce preparation costs, and realize the resource utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330620A_ABST
    Figure CN119330620A_ABST
Patent Text Reader

Abstract

The invention discloses a double-alkali-activated fly ash roadbed cementing material and a preparation method thereof, belongs to the technical field of industrial solid waste resource utilization and road engineering, and solves the technical problem that raw materials such as an exciting agent, a reinforcing agent or cement lime are required to be added in the preparation process of an existing roadbed material. The double-alkali-activated fly ash subgrade cementing material is prepared from, by mass, 30-50 parts of red mud, 25-35 parts of fly ash and 25-35 parts of carbide slag, alkali metal Na2O in the red mud and alkaline earth metal CaO in the carbide slag are subjected to double-alkali compounding to be subjected to an alkali-activated reaction with the fly ash, hydrated calcium aluminosilicate and hydrated sodium aluminosilicate gel substances are generated, the synergistic gelling effect is achieved, and the subgrade subgrade cementing material is prepared. The alkali-activated reaction degree of the fly ash is remarkably improved, and the mechanical property and durability of the roadbed cementing material are greatly improved. According to the invention, the solid waste is completely used as the raw material, no extra exciting agent, reinforcing agent or cement lime or other raw materials need to be added, the preparation cost of the roadbed cementing material is reduced, and the resource utilization of the solid waste is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial solid waste resource utilization and road engineering, and specifically relates to a double-alkali activated fly ash roadbed cementitious material and a preparation method thereof. Background Art

[0002] The production of each square meter of road base material requires about 1.5 to 2 tons of natural sand and soil raw materials, and about 80 to 160 kg of cement or lime. The mining of large amounts of natural sand and soil raw materials causes serious damage to the ecological environment, and the production of cement will cause energy consumption and CO2 emissions.

[0003] Using industrial solid waste instead of natural sand raw materials to prepare roadbed cementitious materials provides an effective way to utilize solid waste resources. The patent document “A roadbed material based on solid waste and a construction method” (publication number: CN111018472 A) discloses that red mud, solid waste (construction waste, waste ore, slag), fly ash, waste gypsum and steel slag powder are used as raw materials, and alkali activator, silica sol, waterproofing agent, fiber, water reducer, modifier and reinforcing agent are added at the same time; the patent document “A cement-lime-phosphogypsum solidified red mud road base mixed blank and preparation method thereof” (publication number: CN115594478 A) discloses that red mud is used as raw material, and cement, lime and phosphogypsum are added as mixed curing agents to synergistically solidify red mud; the patent document “A roadbed filler containing red mud and a preparation method thereof” (publication number: CN 112897977 A) discloses that Bayer red mud, cement, lime powder and phosphogypsum are used as raw materials, and EKS fiber coated with ammonium magnesium sulfate is added at the same time.

[0004] As mentioned above, although solid waste is added during the preparation of existing roadbed materials, activators, reinforcing agents or raw materials such as cement and lime are still required to be added, resulting in high preparation costs. At the same time, industrial solid waste cannot be fully utilized to transform waste into resources. Summary of the invention

[0005] The main purpose of the present invention is to overcome the shortcomings of the prior art and provide a double alkali activated fly ash roadbed cementitious material and a preparation method thereof, which uses red mud, fly ash, and carbide slag as raw materials and does not require the addition of additional activators, reinforcing agents, cement, lime and other raw materials, thereby better realizing the resource utilization of solid waste and reducing the production cost of roadbed materials.

[0006] The present invention is achieved through the following technical scheme: a double-alkali activated fly ash roadbed cementitious material, whose composition and mass fractions are: 30-50 parts of red mud, 25-35 parts of fly ash, and 25-35 parts of calcium carbide slag.

[0007] Furthermore, the red mud, fly ash and carbide slag are all powdered materials obtained after drying and grinding.

[0008] Furthermore, the plasticity indexes of the red mud, fly ash and carbide slag are all between 11 and 17.

[0009] Furthermore, the content of Na2O in the red mud is not less than 16wt%; the content of CaO in the carbide slag is not less than 75wt%; the content of Al2O3 in the fly ash is 22wt%~37wt%, and the content of SiO2 is 43wt%~65wt%.

[0010] Furthermore, the particle size of the red mud is less than 15 μm, the particle size of the fly ash is less than 20 μm, and the particle size of the carbide slag is less than 20 μm.

[0011] A method for preparing a double-alkali activated fly ash roadbed cementitious material comprises the following steps: S1. After fully drying the red mud, fly ash and carbide slag, grind them with a grinder until the particle size of the red mud is less than 15 μm, the particle size of the fly ash is less than 20 μm, and the particle size of the carbide slag is less than 20 μm. Each raw material is weighed for standby use; S2, weighing the raw materials prepared in step S1 according to the composition and mass fraction of the double-alkali activated fly ash roadbed cementitious material, and mixing the raw materials uniformly to obtain a mixed blank; S3, performing a heavy compaction test on the mixed blank prepared in step S2 to determine the optimal moisture content and maximum dry density of the mixed blank, and then determine the amount of water required to add to the mixed blank; S4. Add water to the mixed blank prepared in step S2 according to the amount of water added determined in step S3 and prepare a sample. The obtained sample is subjected to standard curing in a curing box to obtain a double-alkali activated fly ash roadbed cementitious material.

[0012] The beneficial effects of the present invention are: The present invention adopts red mud, fly ash and carbide slag as raw materials, all of which are solid wastes, and does not need to add activators, reinforcing agents or raw materials such as cement lime. Alkali metal Na2O in red mud and alkaline earth metal CaO in carbide slag are combined with fly ash to produce alkali excitation reaction to generate calcium aluminosilicate hydrate (CASH) and sodium aluminosilicate hydrate (NASH) gel substances, thereby achieving synergistic gelling effect. Therefore, the degree of fly ash alkali excitation reaction can be significantly improved, and the roadbed cementitious material is prompted to obtain excellent mechanical properties and durability, which significantly reduces the preparation cost of the roadbed cementitious material and realizes the resource utilization of solid waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a SEM image of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1; Figure 2 This is the XRD pattern of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1. DETAILED DESCRIPTION

[0014] In order to make the technical problems, implementation schemes and advantages to be solved by the invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that the embodiments are only preferred embodiments of the present invention, not all embodiments. Example 1

[0015] A double alkali activated fly ash roadbed cementitious material, the composition and mass fraction thereof are: 40 parts of red mud, the content of Na2O in the red mud is 19.68wt%; 30 parts of fly ash, the content of Al2O3 in the fly ash is 31.6wt%, the content of SiO2 in the fly ash is 50.2wt%; 30 parts of carbide slag, the content of CaO in the carbide slag is 90.35wt%. The red mud, fly ash and carbide slag are all powdered materials obtained after drying and grinding. The particle size of red mud is 10.5μm, the particle size of fly ash is 16.5μm, and the particle size of carbide slag is 11.3μm. The plasticity index of red mud is 12.6, the plasticity index of fly ash is 14.6, and the plasticity index of carbide slag is 13.6.

[0016] A method for preparing a double-alkali activated fly ash roadbed cementitious material comprises the following steps: S1. Dry red mud, fly ash and carbide slag in an oven at 105°C to constant weight, and grind the dried materials in a planetary ball mill for 4 hours to obtain red mud powder with a particle size of 10.5 μm, fly ash with a particle size of 16.5 μm, and carbide slag powder with a particle size of 11.3 μm. Weigh each raw material for later use; S2. According to the composition and mass fraction of the double-alkali activated fly ash roadbed cementitious material, the raw materials prepared in step S1 are weighed, 40 parts of red mud, 30 parts of fly ash, and 30 parts of carbide slag, and the raw materials are mixed evenly to obtain a mixed blank; S3. According to the "Testing Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009) in Part 4 "Sampling, Forming and Curing Test of Inorganic Binder Stabilized Materials" (page 69), "T0804-1994 Compaction Test Method for Inorganic Binder Stabilized Materials" (page 69), the mixed blank prepared in step S2 was subjected to a heavy compaction test to determine that the optimal moisture content of the mixed blank was 23.2% and the maximum dry density was 1.65 g / cm 3 , and then determine that the amount of water required for the mixed blank is 23 parts; S4, adding water to the mixed blank prepared in step S2 according to the amount of water added determined in step S3, and preparing samples according to the sample preparation method of "T0843-2009 Inorganic Binder Stabilized Material Specimen Forming Method (Cylindrical)" (page 83) in Part 4 "Sampling, Forming and Curing Test of Inorganic Binder Stabilized Materials" in "Test Procedures for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009), to prepare cylindrical specimens with a specification of Φ50mm×50mm, and subjecting the obtained specimens to standard curing in a curing box (temperature of 20±2°C, humidity ≥95%), to prepare double alkali activated fly ash roadbed cementitious materials, whose microscopic morphology and phase composition are as follows: Figure 1 and Figure 2 shown.

[0017] In the present invention, the alkali metal Na2O in red mud and the alkaline earth metal CaO in carbide slag are double-alkali compounded to carry out alkali excitation reaction on the active SiO2 and Al2O3 in fly ash to generate hydrated calcium aluminosilicate (CASH) and hydrated sodium aluminosilicate (NASH) gel substances, thus achieving synergistic gelation. The principle is as follows: CaO+H2O=Ca(OH)2; xCa(OH)2+Al2O3+mH2O=xCaO·SiO2·Al2O3·nH2O (CASH); Na2O+H2O=NaOH;yNaOH+SiO2+Al2O3+mH2O=yNa2O·SiO2·Al2O3·nH2O (NASH).

[0018] The double-alkali activated fly ash roadbed cementitious material prepared in this Example 1 was subjected to the following performance tests, and the results are as follows.

[0019] 1. Mechanical properties test of roadbed cementitious materials On the last day of curing for 7 days and 28 days, the cylindrical specimens of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1 were taken out and soaked in water for 24 hours. The unconfined compressive strength, flexural tensile strength and indoor rebound modulus of the specimens after curing were tested. The results are shown in Table 1.

[0020]

[0021] 2. Freeze resistance test of roadbed cementitious materials The cylindrical specimens of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1 were taken out after curing for 28 days to conduct a freeze-thaw cycle experiment. The specific experimental steps were: the specimens were frozen in a -18°C freeze-thaw box for 16 hours, and then placed in (20±2)°C water for thawing for 8 hours, that is, a freeze-thaw cycle was formed. The mass and unconfined compressive strength of the specimens after 5, 10, and 15 freeze-thaw cycles were measured, respectively, and the mass loss rate and strength loss rate of the specimens before and after the freeze-thaw cycle test were calculated. The results are shown in Table 2.

[0022]

[0023] 3. Test on the resistance of roadbed cementitious materials to dry-wet cycles The cylindrical specimens of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1 were taken out for dry-wet cycle experiment after being cured in a curing box for 28 days. The specific experimental steps were: the specimens were dried in a 45°C oven for 12 hours and then immersed in 20°C water for 12 hours, forming a dry-wet cycle. The mass and unconfined compressive strength of the specimens were measured after 5, 10, and 15 dry-wet cycles, respectively, and the mass loss rate and strength loss rate of the specimens before and after the dry-wet cycle experiment were calculated. The results are shown in Table 3.

[0024] Table 3 Data on mass loss rate and residual strength of roadbed cementitious materials before and after dry-wet cycle test

[0025] 4. Heavy metal leaching test of roadbed cementitious materials The cylindrical sample of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1 was taken out after being cured in a curing box for 28 days, and crushed to 1-2 mm. Referring to the "Solid Waste Leaching Toxicity Leaching Method - Horizontal Oscillation Method" (HJ 557-2010), 100 g of the sample was weighed into a 2L extraction bottle, and ultrapure water was added at a solid-liquid ratio of 1:10. At room temperature, the sample was oscillated on a horizontal oscillator at a frequency of (110±10) times / min and an amplitude of 40 mm for 8 hours at a constant temperature, and then allowed to stand for 16 hours. The sample was filtered with a 0.45 μm filter membrane, and the supernatant was taken to determine the concentration of heavy metals. The results are shown in Table 4.

[0026]

[0027] 5. Radioactivity test of roadbed cementitious materials The cylindrical sample of the double-alkali activated fly ash roadbed cementitious material prepared in Example 1 was taken out after being cured in the curing box for 28 days, and the radioactivity was tested. The results are shown in Table 5.

[0028]

[0029] Combining the data in Tables 1 to 5, it can be seen that the cylindrical specimen of the double-alkali activated fly ash roadbed cementitious material prepared in the present embodiment 1 has a 7-day infinite lateral compressive strength of 13.6 MPa, a 7-day flexural tensile strength of 4.07 MPa, and a 28-day indoor compressive rebound modulus of 921.75 MPa; after 15 freeze-thaw cycles, the mass loss rate of the roadbed material is 0.66%, and the strength loss rate is 7.25%; after 15 dry-wet cycles, the mass loss rate of the roadbed material is 0.12%, and the strength loss rate is 1.86%; the heavy metal dissolution and radioactivity of the roadbed material meet the relevant standard requirements of the roadbed material, and can be used as a semi-rigid base material for roads. Example 2

[0030] A double alkali activated fly ash roadbed cementitious material, the composition and mass fraction thereof are: 30 parts of red mud, the content of Na2O in the red mud is 16wt%; 25 parts of fly ash, the content of Al2O3 in the fly ash is 22wt%, and the content of SiO2 in the fly ash is 43wt%; 25 parts of carbide slag, the content of CaO in the carbide slag is 75wt%. The red mud, fly ash and carbide slag are all powdered materials obtained after drying and grinding. The particle size of red mud is 14.5μm, the particle size of fly ash is 15.2μm, and the particle size of carbide slag is 12.6μm. The plasticity index of red mud is 11.3, the plasticity index of fly ash is 12.5, and the plasticity index of carbide slag is 16.8.

[0031] A method for preparing a double-alkali activated fly ash roadbed cementitious material comprises the following steps: S1. Dry red mud, fly ash and carbide slag in an oven at 105°C to constant weight, and grind the dried materials in a planetary ball mill for 4 hours to obtain red mud powder with a particle size of 14.5 μm, fly ash with a particle size of 15.2 μm, and carbide slag powder with a particle size of 12.6 μm. Weigh each raw material for later use; S2. According to the composition and mass fraction of the double-alkali activated fly ash roadbed cementitious material, the raw materials prepared in step S1 are weighed respectively, including 30 parts of red mud, 25 parts of fly ash, and 25 parts of carbide slag, and the raw materials are mixed evenly to obtain a mixed blank; S3. According to "T0804-1994 Compaction Test Method for Inorganic Binder Stabilized Materials" (page 69) in Part 4 "Sampling, Forming and Curing Test for Inorganic Binder Stabilized Materials" of "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009), a heavy compaction test is performed on the mixed billet prepared in step S2 to determine the optimal moisture content and maximum dry density of the mixed billet, and then determine the amount of water required to be added to the mixed billet; S4. Add water to the mixed blank prepared in step S2 according to the amount of water added determined in step S3, and prepare cylindrical specimens according to the sample preparation method of "T0843-2009 Inorganic Binder Stabilized Material Specimen Forming Method (Cylindrical)" (page 83) in Part 4 "Sampling, Forming and Curing Test of Inorganic Binder Stabilized Materials" in "Test Procedures for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009), and perform standard curing of the obtained specimens in a curing box (temperature of 20±2°C, humidity ≥95%) to prepare double alkali activated fly ash roadbed cementitious material. Example 3

[0032] A double alkali activated fly ash roadbed cementitious material, the composition and mass fraction thereof are: 50 parts of red mud, the content of Na2O in the red mud is 21wt%; 35 parts of fly ash, the content of Al2O3 in the fly ash is 37wt%, and the content of SiO2 in the fly ash is 52wt%; 35 parts of carbide slag, the content of CaO in the carbide slag is 85wt%. The red mud, fly ash and carbide slag are all powdered materials obtained after drying and grinding. The particle size of red mud is 7.5μm, the particle size of fly ash is 11.6μm, and the particle size of carbide slag is 9.5μm. The plasticity index of red mud is 13.2, the plasticity index of fly ash is 11.5, and the plasticity index of carbide slag is 14.3.

[0033] A method for preparing a double-alkali activated fly ash roadbed cementitious material comprises the following steps: S1. Dry red mud, fly ash and carbide slag in an oven at 105°C to constant weight, and grind the dried materials in a planetary ball mill for 4 hours to obtain red mud powder with a particle size of 7.5 μm, fly ash with a particle size of 11.6 μm, and carbide slag powder with a particle size of 9.5 μm. Weigh each raw material for later use; S2. According to the composition and mass fraction of the double-alkali activated fly ash roadbed cementitious material, the raw materials prepared in step S1 are weighed, 50 parts of red mud, 35 parts of fly ash, and 35 parts of carbide slag, and the raw materials are mixed evenly to obtain a mixed blank; S3. According to "T0804-1994 Compaction Test Method for Inorganic Binder Stabilized Materials" (page 69) in Part 4 "Sampling, Forming and Curing Test for Inorganic Binder Stabilized Materials" of "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009), a heavy compaction test is performed on the mixed billet prepared in step S2 to determine the optimal moisture content and maximum dry density of the mixed billet, and then determine the amount of water required to be added to the mixed billet; S4. Add water to the mixed blank prepared in step S2 according to the amount of water added determined in step S3, and prepare cylindrical specimens according to the sample preparation method of "T0843-2009 Inorganic Binder Stabilized Material Specimen Forming Method (Cylindrical)" (page 83) in Part 4 "Sampling, Forming and Curing Test of Inorganic Binder Stabilized Materials" in "Test Procedures for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009), and perform standard curing of the obtained specimens in a curing box (temperature of 20±2°C, humidity ≥95%) to prepare double alkali activated fly ash roadbed cementitious material.

[0034] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A double alkali activated fly ash roadbed cementitious material, characterized in that: The composition and mass proportions of the double-alkali activated fly ash roadbed cementitious material are: 30-50 parts of red mud, 25-35 parts of fly ash, and 25-35 parts of carbide slag.

2. The double-alkali activated fly ash roadbed cementitious material according to claim 1, characterized in that: The red mud, fly ash and carbide slag are all powdered materials obtained through drying and grinding.

3. A double-alkali activated fly ash roadbed cementitious material according to claim 1 or 2, characterized in that: The plasticity indexes of the red mud, fly ash and carbide slag are all between 11 and 17.

4. A double-alkali activated fly ash roadbed cementitious material according to claim 1 or 2, characterized in that: The content of Na2O in the red mud is not less than 16wt%; the content of CaO in the carbide slag is not less than 75wt%; the content of Al2O3 in the fly ash is 22wt%~37wt%, and the content of SiO2 is 43wt%~65wt%.

5. A double-alkali activated fly ash roadbed cementitious material according to claim 1 or 2, characterized in that: The particle size of the red mud is less than 15 μm, the particle size of the fly ash is less than 20 μm, and the particle size of the carbide slag is less than 20 μm.

6. A method for preparing a double-alkali activated fly ash roadbed cementitious material as claimed in claim 1, characterized in that: The following steps are involved: S1. After fully drying the red mud, fly ash and carbide slag, grind them with a grinder until the particle size of the red mud is less than 15 μm, the particle size of the fly ash is less than 20 μm, and the particle size of the carbide slag is less than 20 μm. Each raw material is weighed for standby use; S2, weighing the raw materials prepared in step S1 according to the composition and mass fraction of the double-alkali activated fly ash roadbed cementitious material, and mixing the raw materials uniformly to obtain a mixed blank; S3, performing a heavy compaction test on the mixed blank prepared in step S2 to determine the optimal moisture content and maximum dry density of the mixed blank, and then determine the amount of water required to add to the mixed blank; S4. Add water to the mixed blank prepared in step S2 according to the amount of water added determined in step S3 and prepare a sample. The obtained sample is subjected to standard curing in a curing box to obtain a double-alkali activated fly ash roadbed cementitious material.

Citation Information

Patent Citations

  • Roadbed material based on red mud and solid waste and construction method thereof

    CN111018472A

  • Red mud-containing roadbed filler and preparation method thereof

    CN112897977A

  • Cement-lime-ardealite cured red mud road base mixture and preparation method thereof

    CN115594478A